2021
DOI: 10.1007/s40843-021-1762-0
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine additive engineering enables improved film formation towards high efficiency and moisture stability in perovskite solar cells

Abstract: Perovskite solar cells (PSCs) attract widespread research interest due to their exceptional properties. However, the instability of the perovskite layer, especially the moisture instability, and existing defects seriously restrict the performance and limit the development of PSCs towards commercialization. Herein, we fabricate moisture-stable and efficient PSCs by incorporating a thiamine (THM) additive into a lead iodide (PbI 2 ) precursor using a two-step spin-coating method. This strategy enables a better i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…MA 0.5 FA 0.5 PbI 3 HPs thin films synthesized with thiamine were found to coordinate through the A site cation rather than through the B site, and exhibited improved crystallinity, a reduction in defect states, and improved charge extraction efficiency when incorporated into thin film PVs, with a PCE of 21.40%. 180 The authors also observed increased moisture resistance, which they attribute to the formation of a hydrophobic barrier by outward-facing thiamine molecules. As such, the introduction of thiamine to this HP composition appears to improve the optical properties, suggesting the use of organic antioxidants, such as vitamins, can be beneficial for both HPNC and HP thin film synthesis.…”
Section: Perovskite Thin Filmsmentioning
confidence: 96%
“…MA 0.5 FA 0.5 PbI 3 HPs thin films synthesized with thiamine were found to coordinate through the A site cation rather than through the B site, and exhibited improved crystallinity, a reduction in defect states, and improved charge extraction efficiency when incorporated into thin film PVs, with a PCE of 21.40%. 180 The authors also observed increased moisture resistance, which they attribute to the formation of a hydrophobic barrier by outward-facing thiamine molecules. As such, the introduction of thiamine to this HP composition appears to improve the optical properties, suggesting the use of organic antioxidants, such as vitamins, can be beneficial for both HPNC and HP thin film synthesis.…”
Section: Perovskite Thin Filmsmentioning
confidence: 96%
“…17,18 The V OC is influenced not only by defect-related non-radiative recombination, but also by the energy band mismatch caused by Rb 2 SO 4 . 18,19 The performance statistics results of 20 devices shown in Fig. S20 (ESI †) and Table S5 (ESI †) indicate that the control devices and the target devices both show good reproducibility and the average PCE of the target device (21.52%) is better than that of the control device (19.90%).…”
Section: àmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In recent years, organic-inorganic hybrid perovskite materials have been used as active layers in photodetectors owing to their strong light absorption, high carrier mobility, good mechanical flexibility, and solution preparation. [9][10][11][12][13][14] Owing to the tunable bandgap of perovskites, many nanoimprinting to improve crystal quality and successfully realized a high-performance CsPbI 3 -CsPbBr 3 lateral heterojunction photodetector. [28] The high-crystal-quality film suppressed the recombination of charge carriers at the lateral heterojunction induced by the grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–8 ] In recent years, organic–inorganic hybrid perovskite materials have been used as active layers in photodetectors owing to their strong light absorption, high carrier mobility, good mechanical flexibility, and solution preparation. [ 9–14 ] Owing to the tunable bandgap of perovskites, many new material systems can form heterostructures with perovskites to improve device performance. [ 15–17 ] For example, Dou et al.…”
Section: Introductionmentioning
confidence: 99%